A Method for Calculating the Real Value of Equity by Identifying Toxic Assets in the Reports of Professional Participants of the Securities Market - Borodin, Alexander; Shamin, Vadim; Shamina, Irina (Olsztyn Economic Journal, 2018)
This article is devoted to a comprehensive study of toxic assets, which are on the balance sheets of professional securities market participants, in order to calculate the real value of capital. The authors have developed a method similar to a formalized algorithm for identifying toxic assets of liquidating or liquidated companies and assets in credit institutions with a revoked license, for subsequently adjusting the value of equity (net assets), and analyzing for compliance with the Bank of Russia supervisory requirements. The method is described by the authors in accordance with BPMN notation. The authors determined the information base of the method, which includes only mandatory reporting and open information resources, which makes it simple and transparent for users. Prospective users of the method may be the Bank of Russia, current and future counterparties of professional participants in the securities market, DBMS developers and scientific employees of economic specialties. The method was tested by the authors on the basis of a real-life brokerage company.